The determination of the airway receptors involved in trachea relaxant properties of aqueous tiger milk mushroom - Kamaruddin, Nurul Iffah (2022)
Asthma is "a heterogeneous disease" that has been considered a severe public health concern, usually characterized as a chronic inflammatory disease of the airways, and producing intermittent breathing difficulties. Exposure to trigger factors such as sensitizing inhaled allergens or other environmental irritants results in bronchoconstriction of the lining of the bronchial tubes. Asthma could be characterised by reversible airflow obstruction, airway inflammation, mucus hypersecretion, and AHR. Tiger milk mushroom, known as Lignosus rhinoceros, has traditionally been used for asthma medication. Therefore, it is essential to determine the receptor involved in the Tiger Milk Mushroom mechanism on airway hyperresponsiveness. The main objective of this study was to determine the airway receptors involved in trachea relaxant properties of aqueous Tiger Milk Mushroom in the isolated guinea-pig trachea (GPT) through an agonist-antagonist study. A hot Soxhlet extraction process was used to prepare Tiger Milk Mushroom extracts. In a functional myograph study, the isolated GPT was utilized to compare the relaxant properties of Tiger Milk Mushroom extract to the non-selective muscarinic antagonist, atropine, on carbachol-induced contractile (non-selective muscarinic agonist) tone. Tiger Milk Mushroom partially relaxed the carbachol-induced contraction of the isolated GPT at a higher concentration (1 g/ml) in 10 μM with established pIC50 of 1.42 ± 0.21. Atropine elicited complete relaxation at 100 μM with pIC50 of 3.91 ± 0.64. In conclusion, this study reveals that the Tiger Milk Mushroom partially possessed a direct tracheal relaxant through the muscarinic receptor.